Desain dan Analisis Kinerja Air Blower Kipas Sentrifugal untuk Pengendalian Gulma - Pramuhadi, Gatot; Ayu, Zavira Mega; Sidik, Ahmad Jaelani (abe.fp.unila.ac.id, 2024)
This study aims to design and analyze the performance of the centrifugal fan water for weed control and compare it with the performance of air blowers that use axial fans. This study consists of three stages, namely design and manufacturing, testing in the laboratory, as well as testing for controlling dry land weeds in the field. There are 6 treatments tested, namely a combination of two types of fans (axial and centrifugal) and three types of cone nosel (4 holes, 5 holes, and 6 holes). The results showed that the centrifugal fan air blower displays good performance according to functional design and structural design. Centrifugal fan blower performance is more effective than axial fan air blower because centrifugal fan blower is able to produce smaller (smoother) droplet diameters and larger droplet density (more tight) so that it has a greater herbiciding ability than axial fan air blower water . Centrifugal fan blower can produce a droplet diameter of 94 microns to 118 microns more fine than axial fan of 246 microns to 299 microns. The centrifugal fan blower can produce a larger droplet density (tight) of 369 droplets/cm2 to 538 droplets/cm2 compared to the axial fan of 74 droplets/cm2 to 117 droplets/cm2. The centrifugal fan blower water produces a spraying discharge of 1.22 liters/minute to 1.41 liters/minute is smaller than the axial fan of 2.33 liters/minute to 2.93 liters/minute. The ability of centrifugal fan herbiciding is 76.21% to 78.02% greater than axial fan of 76.36% to 77.41%. Keywords: Air Blower, Axial Fan, Centrifugal Fan, Herbiciding, Weeds